Percutaneous coronary interventions in patients over 80 years old age with acute coronary syndrome - A. Alexandrov; H. Mateev; G. Vladimirov; I. Bayraktarova; I. Petrova; E. Kostova-Dimitrova (Българска кардиология, 2023)
Age is an important non-modifi able risk factor for cardiovascular disease. Both European and American guidelines recommend offering an invasive reperfusion strategy in elderly patients with ACS, taking into account the patients‘ comorbidities and baseline level of functioning. Materials and methods: All patients over 80 years of age with acute coronary syndrome, treated in the Department of Invasive Cardiology of the National Heart Hospital for the period between January 1, 2016. and December 31, 2018, are retrospectively analyzed. The primary endpoint was defi ned as all-cause mortality during the hospital stay and at follow-up. Predictors of mortality were assessed and independent predictors were identifi ed. Results: During the study period, 179 patients aged 80 years or older were identifi ed as being treated for ACS with PCI. In the study population, in hospital mortality for the index event was 11.8%. At a mean follow-up time of 20.19 ± 11.9 months, mortality rose signifi cantly to 64.6%. When evaluating in-hospital mortality on multivariate analysis, the two independent predictors were Cardiogenic shock (HR 0.005, 95% CI 0.01–0.44; p < 0.001) and acute/exacerbated renal failure (0.986 95% CI 0.984-0.997; p = 0.015). Conclusion: The present study provides important information regarding characteristics and outcomes in very elderly patients undergoing PCI for ACS. In the future, this subset of patients is predicted to grow, meaning that their approach must be evidence-based to ensure safe and effective treatment options.